Electrical properties of mixed oxides of manganese and vanadium prepared by conventional solid state and mechanical alloying methods - Tan, Foo Khoon (2016)
Metal oxide of manganese (Mn) and vanadium (V) are widely studied due to their interesting fundamental physical properties. There were several works on Mn-V mixed oxide done previously, but it still lacks comprehensive electrical studies on Mn-V oxide system which can gives more information to describe the mixed oxide. In this project, the investigation toward morphology, electrical conductivity, dielectric properties and thermal diffusivity of the mixed oxides was carried out. The samples were prepared by conventional solid state (SS) and mechanical alloying (MA) methods. The samples were prepared with a ratio of 40 mol% of V2O5 and 60 mol% of 2MnO2 and were sintered at different sintering temperatures from 500 to 800oC and characterized. In the meantime, samples of pure oxides, Mn and V were also prepared to compare with the mixed oxides. X-ray Diffraction confirmed that the samples prepared are multi phases and Rietveld refinement method was employed to estimate the phase composition in each sample. MA method successfully reduced the sintering temperature for the reaction to occur at a much lower temperature compare to SS method. Also, the surfaces of the sample were visualized using Field emission scanning electron microscopy (FESEM) and the average grain size was calculated. From FESEM images, MA method produced very fine particles in nano-scale while SS method in micro-scale. The DC and AC conductivities of the samples showed the semiconducting behavior because the electrical conductivity increases when temperature increased. The Mn-V oxides have lower electrical conductivity as compare to the starting materials. Since the samples are multi phases, hence the dielectric constant obtained is a contribution from different phases. The polarization mechanism in this frequency region (40 to 1 MHz) can be explained by interfacial and dipolar polarization. On the other hand, the spectra of electric modulus and impedance of the samples successfully revealed the dielectric relaxation process which cannot be observed directly from dielectric loss spectrum. Equivalent circuit modeling was adopted to further describe and predict the electrical properties of the material. The samples were successfully fitted to single parallel RC circuit or two parallel RC circuits connected in series. The sample sintered at 500oC prepared using MA method gave the best dielectric properties. This is possibly due to MA method reduces the particle size and increases the grain boundary volume of the sample. Also, the MA series have better thermal stability and gave higher thermal diffusivity compare to SS series where the heat from energy dissipation can be easily transferred for the cooling process. Lastly, a more comprehensive electrical and thermal study on Mn-V oxide system is done and it can be a reference for future researchers.